2014
DOI: 10.4236/health.2014.620317
|View full text |Cite
|
Sign up to set email alerts
|

Conformity to Traditional Gender Norms in a Feminized Occupation: The Influence on Health Behaviors

Abstract: The object of this study is to examine the relationships between conformity to traditional gender norms and health in a special group of the Spanish population, male/female nurses. Nursing is a particularly good example of feminized occupation. Spanish male (n = 98) and female (n = 98) nurses matched in diverse sociodemographic variables complete measures of gender norms and health behavior variables. Measures of conformity to gender norms in female and male nurses are compared with those of the general popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…11 A study conducted in Spain showed that female nurses (n = 98) working in public hospitals reported higher levels of perceived stress and higher levels of plasma-extracted cortisol than male nurses (n = 98). 12 Finally, a 1-year German longitudinal study involving 70 physicians (mean age 30 years, 40 women) suggested that longer shift hours were associated with changes in the diurnal cortisol pattern. 13 Studies of stress among female healthcare professionals that measure levels of cortisol are scarce.…”
mentioning
confidence: 99%
“…11 A study conducted in Spain showed that female nurses (n = 98) working in public hospitals reported higher levels of perceived stress and higher levels of plasma-extracted cortisol than male nurses (n = 98). 12 Finally, a 1-year German longitudinal study involving 70 physicians (mean age 30 years, 40 women) suggested that longer shift hours were associated with changes in the diurnal cortisol pattern. 13 Studies of stress among female healthcare professionals that measure levels of cortisol are scarce.…”
mentioning
confidence: 99%
“…This study has the following limitations: ESS data is based on self-reported measures and, although most of the information is correct, there may be mistakes and false reported information, namely regarding income; there is also the possibility of some bias resulting from refusal to participate in some social groups in different countries (Alam et al 2005;Demarest et al 2013;Stoop 2005); finally, some variables, namely, "subjective general health", in ESS, adopted a five-point scale, which is easier from the respondent's point of view, but gives the researcher fewer opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…asymmetric distribution of household, children and familial care), along with those stemming from the nursing profession (14).…”
Section: Discussionmentioning
confidence: 99%
“…With the present work, our aim is to confirm that male and female nurses have worse mental health than the general Spanish population (13,14). The second point is to verify whether mental health, as measured by means of the 12-item GHQ-12, is worse among female nurses than male ones.…”
Section: Objectivesmentioning
confidence: 99%